An Analysis of the Non-English Department Students’ Speaking Ability at Universitas Riau - Rukmaryadi Rukmaryadi (International Journal of Educational Dynamics, 2020)
This article to analyze and describe the speaking ability of non-English department students, Universitas Riau in the academic year 2016/2017 covering pronunciation, grammar, vocabulary, fluency and comprehension. The study was also aimed to describe the activities done by the English lecturer in the teaching and learning process and the difficulties the students had when speaking. Descriptive qualitative method was used in this study participated by twenty participants at the Faculty of Economics Universitas Riau. The data were gathered using observation, an oral test in the form of interview and documentation. The results of the data analysis of the participants’ speaking ability in terms of pronunciation indicated that 11 participants’ pronunciation was in fair category, 7 participants’ pronunciation was in very good category, 2 participants’ pronunciation was in very good category and none of the participants’ pronunciation was in poor and excellent categories. In terms the participants’ speaking ability in grammar, the findings showed that 12 participants’ grammar was in fair category, 6 was in good category, 2 was in very good category, and none was in poor and excellent categories. In terms of the participants’ speaking ability in vocabulary, it was discovered that 2 participants’ vocabulary was in poor category, 4 was in good category, 14 was in fair category, and none was in very good and excellent categories. The participants’ speaking ability in terms of fluency, the findings revealed that 2 participants’ speaking ability was in poor category, 5 was in good category, 13 was in fair category, and none was in very good and excellent categories. Finally, the participants’ speaking ability in terms of comprehension indicated that 2 participants’ comprehension was in poor category, 4 was in good category, 14 was in fair category, and none was in very good and excellent categories